(untitled) (Scientific journal of the Fergana State University, 2023)
In addition to the importance of multimedia storitelling in the teaching of philosophy in modern higher education today, the article provides information about the concept of storitelling, the history of its creation, its components, principles, services used in it. The study of the basics of creating multimedia storitelling is explained by the fact that professors of philosophy are not only studying new technologies, but also learning to attract all interested people from all over the world through a global network to their material.